Adaptive scanning methodology for object‐oriented visual information processing. Issue 10 (1st May 2013) - Chew, Li Wern
Abstract : The raster scan method in visual information processing is the rectangular pattern of image capture and reconstruction which systematically covers the area progressively, one line at a time starting from the top left corner. This traditional scanning method might work well for still image processing but for moving images, a scanning method such as diagonal snake scan can provide a better object correlation in a sequence of image frames. A novel adaptive scanning method for object‐oriented visual information processing is proposed. Here, image pixels are collected starting from the centre of the image area and progressively extended outwards similar to the water drop ripple effect. Simulation results have shown that the proposed work uses up to 33% less processing time to cover the region‐of‐interest in an image compared to the raster scan method. Preliminary simulation results have also shown that with the proposed adaptive scanning methodology, there is a significant improvement in the performance of the object‐oriented visual compression.